THE EFFECT OF BUILDING HEIGHT AND SHEAR WALL LOCATION ON MULTISTOREY REINFORCED CONCRETE STRUCTURE - Alexander Lyman, Regan
In designing high-rise buildings, seismic loads are very important to be considered, to stiffen and strengthen the structure, structural elements that effectively can resist lateral loads due to earthquakes is needed which is shear wall. On high-rise buildings, shear wall and frames can interact to resist lateral loads that occur. Therefore, in this final project, the writer wants to know more about the interaction between shear wall and frames on multistorey reinforced concrete structure, both for high-rise and low-rise buildings and the location of shear wall on the right as freestanding shear wall also shear wall on the left as framed shear wall. The indicators used to observe are the comparison of shear and moment forces on shear wall to frames, the comparison of shear and moment forces on near columns to far columns from the shear wall. The structure is modeled on ETABS v18.1.1. Based on the analysis results, it was found that framed shear wall resists more shear forces than freestanding shear wall for both low-rise and high-rise Buildings. Then, the columns that is far away from the shear wall will resist more shear and moment forces also the inflection point will decrease on higher floors. The beams connected directly to the shear wall will resist more moment forces. The relative stiffness of the shear wall is the largest compared to other columns’ relative stiffness. Last, the location of the resultant earthquake forces that occur does not work at the building’s center of mass so that causes the joint drift of the reference point has different values.